2019
DOI: 10.3390/app9112233
|View full text |Cite
|
Sign up to set email alerts
|

Mode-Selective Photonic Lanterns for Orbital Angular Momentum Mode Division Multiplexing

Abstract: We analyze the mode evolution in mode-selective photonic lanterns with respect to taper lengths, affected by possible mode phase differences varying along the taper. As a result, we design a three-mode orbital angular momentum (OAM) mode-selective photonic lantern by optimizing the taper length with mode crosstalk below −24 dB, which employs only one single mode fiber port to selectively generate one OAM mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…FMFs on the other hand show no such drift, since the modes propagate in the same core (See Supplemental material), showing they may be ideal for this application. Other recently demonstrated lanterns have had losses as low as 0.7 dB for a 6-mode lantern [44], with recent simulations point- ing out that lanterns of much lower losses (0.1 dB) could be reached [38], further demonstrating the attractiveness of our scheme over time-bin encoding for quantum communication.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…FMFs on the other hand show no such drift, since the modes propagate in the same core (See Supplemental material), showing they may be ideal for this application. Other recently demonstrated lanterns have had losses as low as 0.7 dB for a 6-mode lantern [44], with recent simulations point- ing out that lanterns of much lower losses (0.1 dB) could be reached [38], further demonstrating the attractiveness of our scheme over time-bin encoding for quantum communication.…”
supporting
confidence: 53%
“…The states |OAM ± are associated to the well known Laguerre-Gaussian beams carrying orbital angular momentum (OAM) [38]. Figure 2a shows the theoretical transverse intensity profiles of the |LP 11a and |LP 11b modes as well as experimental results in the back-toback case and after 500 m of propagation, obtained with a linear polariser and an infrared CCD camera placed after the FMF link.…”
mentioning
confidence: 99%
“…The fused coupler technique is employed in making mode-selective photonic lanterns (MSPLs) exciting five OAM modes in a ring core fiber with a bandwidth of 500 nm (1000 to 1500 nm). 143 More recently, Li et al 144 have reported on the simulation of MSPL for three OAM modes with a modal cross talk of less than −24 dB. Such results help in highlighting the immense potential of the mode-selective fused fiber coupler approach for the generation of desired OAM modes.…”
Section: Hybrid Approachmentioning
confidence: 93%
“…The single-mode LO beam is split into N equal parts by a fiber beam splitter (FBS). Each single-mode 1 There are two types of PLs [26], [27]: mode-selective PL [28], [29] and non-mode-selective PL [20]- [23]. In a mode-selective PL, the single-mode cores are designed for transmitting light with different electromagnetic wave modes.…”
Section: Smf Receiver Mmf Receivermentioning
confidence: 99%